Penerapan Media Aplikasi Fun Easy Learning Terhadap Penguasaan Kosakata Peserta Didik Di Mts Darul Jalal - St Hayatunnisa; Hanafi Hanafi (Journal on Education, 2024)
The use of learning media has a crucial role in the implementation of the teaching and learning process, with adjustments to the use of media that consider the needs of students to make it easier for them to follow each sub-learning. One form of learning media that can be used is the Fun Easy Learn application, which is specifically designed to provide a word play experience to improve understanding and fluency in learning Arabic. This application is an interesting educational game, presenting various games such as matching words, completing words, and others. All these games are designed to stimulate all the senses of the learner, helping students understand Arabic more easily. The main goal is to make it easier for students in MTs Darul Jalal to develop mastery of Arabic vocabulary. The purpose of this study is to evaluate the extent of the impact of Fun Easy Learning application media on the mastery of mufrodat in students in MTs Darul Jalal. The research approach used is qualitative, with literature review as the data collection stage. The process of data analysis involves interviews, observation, and documentation. The results showed that the application of learning media, especially using the Fun Easy Learning application, proved effective in increasing students' understanding of mufrodite. There are factors that influence outcomes, such as variations in student learning styles, including visual, kinesthetic, and auditory styles, that need to be adjusted to the type of learning media used.